2002
DOI: 10.1093/brain/awf016
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative mapping of the subcortical language pathways using direct stimulations

Abstract: Functional neuroimaging has improved pre-planning of surgery in eloquent cortical areas, but remains unable to map white matter. Thus, tumour resection in functional subcortical regions still presents a high risk of sequelae. The authors successfully used intraoperative electrical stimulations to perform subcortical language pathway mapping in order to avoid postoperative definitive deficit, and correlated these functional findings with the anatomical location of the eloquent bundles detected using postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
308
0
29

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 518 publications
(360 citation statements)
references
References 50 publications
23
308
0
29
Order By: Relevance
“…The large number of stimulation sites was used so that we could study the roles of all the available regions (the inferior parietal lobule, right angular gyrus and superior temporal gyrus) in simple arithmetic. The stimulation-site density was based on previous studies (e.g., Duffau, 2007;Duffau et al, 2002). After locating the tumor boundaries, sterilized paper with printed numbers were placed on the cortical surface to mark the 47 stimulation sites.…”
Section: Cortical Stimulation During Operationmentioning
confidence: 99%
See 3 more Smart Citations
“…The large number of stimulation sites was used so that we could study the roles of all the available regions (the inferior parietal lobule, right angular gyrus and superior temporal gyrus) in simple arithmetic. The stimulation-site density was based on previous studies (e.g., Duffau, 2007;Duffau et al, 2002). After locating the tumor boundaries, sterilized paper with printed numbers were placed on the cortical surface to mark the 47 stimulation sites.…”
Section: Cortical Stimulation During Operationmentioning
confidence: 99%
“…To our knowledge, no study has used the intraoperative cortical stimulation approach to investigate the role of the right parietal cortex in numerical processing. Previous studies only examined the left parietal cortex (e.g., Duffau et al, 2002;Roux et al, 2009;Whalen et al, 1997). Given previous imaging findings of a neural dissociation in the right parietal region mentioned above (Prado et al, in press;Zhou et al, 2007), we expected that subtraction, but not multiplication, would be affected when the right parietal lobe was stimulated.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The arcuate fasciculus is classically linked to language, and it has been demonstrated that stimulation in different parts of this structure generates different expressions including phonemic paraphasias, and disorders that affect the formation of phonological words 5 . Currently it is recognized that the arcuate fasciculus that connects the parietal and temporal regions of the frontal lobe is composed of various subcomponents.…”
Section: Introductionmentioning
confidence: 99%